2004
DOI: 10.1007/s00468-004-0401-4
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of carbon and nitrogen distribution and composition, photochemical efficiency and stable isotope ratios in Araucaria angustifolia

Abstract: Araucaria angustifolia (Bertol.) Kuntze is an indigenous conifer restricted to the southern region of South America. In this on-site field study, we provide a detailed description of the nitrogen compounds and sugars allocated to the different plant compartments in tall adult trees, young trees about 2-3 m tall and small seedlings at its northernmost occurrence in the mountains of Itatiaia (20 • 25 S; 44 • 50 W; 2,000 m a.s.l.), SE Brazil. We determined C and N contents, soluble sugars, soluble non-protein N-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 46 publications
(52 reference statements)
1
19
1
Order By: Relevance
“…These results support the suggestions made by Franco et al (2005) that most of the N taken up from the soil is metabolized in the roots, and is consistent with the results of Duarte and Dillenburg (2000), who detected NRA only in the roots of A. angustifolia. Our study to the best of our knowledge, presents the first evidence of leaf NRA in this species.…”
Section: Discussionsupporting
confidence: 92%
“…These results support the suggestions made by Franco et al (2005) that most of the N taken up from the soil is metabolized in the roots, and is consistent with the results of Duarte and Dillenburg (2000), who detected NRA only in the roots of A. angustifolia. Our study to the best of our knowledge, presents the first evidence of leaf NRA in this species.…”
Section: Discussionsupporting
confidence: 92%
“…On one hand, this may be a result of a higher lipid content in the membrane-rich chloroplasts, as it has been reported that lipids are depleted in 13 C compared with organic matter, acids, sugars and respired CO 2 (Hobbie and Werner 2004). On the other hand, during the transport of organic C from leaves to roots, metabolic branching may result in C isotope fractionation and 13 C enrichment of sugars in sink when compared with source tissues (Damesin and Lelarge 2003;Franco et al 2005). …”
mentioning
confidence: 99%
“…Plants, in general, have an optimal as well as minimum and maximal air temperature for vegetative growth (McClung and Davis 2010;Hatfield and Prueger 2015). Although A. angustifolia occurs in high latitudes and/or high altitudes (Franco et al 2005;Duarte et al 2006), which reinforces that its growth and success may be associated with low temperatures, there are no studies showing the optimum temperature range for the vegetative growth of this species, making a contrast with studies of seed germination of this species. For seed germination of A. angustifolia, it has been demonstrated that the optimum temperature varies between 20 and 25°C (Kissmann and Habermann 2014).…”
Section: Discussionmentioning
confidence: 91%
“…Few ecophysiological studies have been conducted with this species, focusing on its response to contrasting irradiance (Duarte and Dillenburg 2000), soil compaction, water relations (Mósena and Dillenburg 2004;Cassana and Dillenburg 2013;Cassana et al 2015), as well as comparisons between young and adult trees in the field (Franco et al 2005). Studies about the effects of increasing temperature on the physiology of A. angustifolia are important, even though this species is associated with cool and moist conditions of subtropical climate.…”
Section: Introductionmentioning
confidence: 99%